PERAN INSEMINASI BUATAN (IB) TERHADAP PENINGKATAN POPULASI TERNAK SAPI DI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG: THE ROLE OF ARTIFICIAL INSEMINATION (AI) IN THE INCREASE OF CATTLE POPULATION IN IV NAGARI DISTRICT SIJUNJUNG REGENCY - Arezhi, Abdi Alva; Alisia, Rini; Maiyontoni, Maiyontoni; Komala, Refika; Meidita, Fadilla (Universitas Boyolali, 2025)
The increasing demand for animal protein from beef has not been matched by a proportional rise in cattle populations in Indonesia, necessitating strategies such as artificial insemination (AI) to accelerate reproduction. This study aimed to evaluate the success of AI programs in increasing cattle populations in IV Nagari District, Sijunjung Regency, by analyzing Non-Return Rate (NRR), Service per Conception (S/C), and Conception Rate (CR). A survey method was employed using primary data (farmer interviews) and secondary data (Puskeswan medical records from 2019–2023). The results showed NRR ranged from 69.80% to 77.91%, indicating a high pregnancy rate after the first AI, S/C for Bali and Ongole cattle averaged 1.13–1.30, reflecting efficient AI implementation, and CR reached 77.7%, exceeding the national standard (60–70%). In conclusion, the AI program in IV Nagari District successfully increased cattle populations, as evidenced by optimal NRR, S/C, and CR values. This success was influenced by inseminator training, farmer awareness, and AI infrastructure support.